Relationship between exercise beliefs, happiness, quality of life and sociodemographic characteristics in pregnant women in Eastern Turkey: a cross-sectional study - Taskaya, Burhan; Ciftci, Necmettin; Durmus, Mustafa; Sahin, Fatih; Yildiz, Metin; Yildirim, Hilal (Bmj Publishing Group, 2025)
Objective This study was conducted to examine the relationship between exercise health beliefs, happiness and quality of life among pregnant women, and to evaluate how sociodemographic characteristics are associated with these variables. Design The study was conducted using a cross-sectional descriptive study design. Data were collected through face-to-face interviews using a convenience sampling approach. 'Personal Information Form', 'Exercise Health Belief Model Scale', 'Oxford Happiness Scale Short Form' and 'Short Form (SF-12) Quality of Life Scale' were used to collect data. Descriptive statistics (mean, SD, percentage), Pearson correlation analysis and simple linear regression were applied. Setting The study was conducted at Family Health Centres located in a provincial centre in Eastern Turkey. Participants A total of 1090 pregnant women who visited the Family Health Centres participated in the study. Results The mean score for the Exercise Health Belief Model Scale was 113.98 +/- 20.49, the mean score for the Oxford Happiness Scale Short Form was 18.45 +/- 4.05 and the mean score for the SF-12 Quality of Life Scale was 85.34 +/- 10.29. A positive and moderately significant correlation was found between exercise health beliefs, happiness and quality of life (r=0.31-0.38, p<0.01). Regression analyses showed that exercise health beliefs were significantly associated with both happiness (R-2=0.097, p<0.01) and quality of life (R-2=0.147, p<0.01). Conclusions Higher levels of exercise health beliefs were associated with increased happiness and quality of life in pregnant women. These findings suggest that nursing interventions aimed at strengthening exercise beliefs may contribute to maternal well-being during pregnancy.
Keywords: Primary Prevention; Health; Attitude; Cross-Sectional Studies; Exercise